TEH CANG SALAK : TEH DARI LIMBAH KULIT SALAK DAN KAYU SECANG YANG BERPOTENSI UNTUK PENCEGAHAN DAN PENGOBATAN PENYAKIT DEGENERATIF - I Wayan Karta; Putu Annand Kurnia Iswari; Luh Ayu Nanamy Khrisnashanti Eva Susila (Meditory : The Journal of Medical Laboratory, 2019)
This study aims to treat salacca peel and secang wood waste into herbal tea and analyze the phytochemical content and antioxidant capacity and organoleptic test of the products made. Salak skin waste samples were taken at the salak center in Sibetan Village and secang wood obtained in Tenganan Village, Karangasem. Antioxidant capacity testing was carried out in the Laboratory Service Unit of the Faculty of Agricultural Technology at UNUD, and phytochemical tests at the Health Polytechnic Department of Denpasar. Organoleptic tests were carried out on 20 panelists. Tea is made by mixing secang wood powder which has been mashed with salak skin powder using 3 variations, namely VR1 (1.5 gram: 0.5 gram), VR2 (1gram: 1 gram), VR3 (0.5 gram: 1.5 gram) ), then soaked in hot water and analyzed.The results showed that Cang Salak Tea with variations of VR1, VR2, and VR3 has active phytochemical content of flavonoids, tannins, alkaloids, terpenoids, and phenols. These compounds have the potential for degenerative diseases. Antioxidant capacity in VR1, VR2, and VR3 are 343.88; 183.88, and 92.12 mg / L GAEAC. The difference in content is caused by the presence of antioxidants in higher secang wood compared to bark. The tea has the potential to be developed into an antioxidant drink which is useful for the prevention and control of degenerative diseases. Organoleptic tests showed that Cang Salak tea products with various variations were favored by panelists. The most preferred color is in VR1, the aroma is on VR3, and it feels on VR2. Future studies require strength tests of antioxidant activity and in vitro or in vivo testing of Cang Salak tea for degenerative diseases